Sistem Pakar Metode Forward Chaining untuk Mengukur Keparahan Penyakit Gigi dan Mulut - Ilham Roni Yansyah; S Sumijan (Jurnal Sistim Informasi dan Teknologi, 2021)
Teeth and mouth are parts of the body that cannot be separated, where the teeth are in the oral cavity so that if there is interference with the teeth it will affect the mouth. Knowledge to recognize dental and oral diseases from an early age is very much needed to be able to maintain healthy teeth and mouth. Lack of knowledge about these oral and dental diseases will result in severe damage to teeth and mouth. This study aims to measure the severity of oral disease and provide a diagnosis of oral and dental disease so that later it can be used as a reference for consultation with a doctor. The method used in this research is Forward Chaining to represent the rules of 27 symptom facts and 8 diseases described by experts. The results of testing for this method are as many as 10 patient data were diagnosed to get the same result as the doctor's analysis so that the accuracy rate is 80%. The expert system designed with the Codeigniter Framework can provide insight by being able to identify the disease suffered by patients and measure the severity of the oral and dental disease suffered